Reconciling International Climate Law and the Energy Charter Treaty through Integrative Interpretation in Arbitration - Miebaka Nabiebu; Ntamy Agube; Mokutima Etido Ekpo (Law and Social Justice in Society, 2026)
The Energy Charter Treaty (ECT) aims to protect energy investments, including fossil fuels, while international climate law seeks to mitigate climate change two objectives that can come into conflict in investor-state dispute settlement (ISDS). Given the unlikelihood of ECT modernization or termination in the near future, arbitration under the treaty will continue to shape the legal landscape of energy investments. This article explores the potential of integrative interpretation as a means to reconcile climate obligations with ECT protections in arbitration. Integrative interpretation is not only mandated by international treaty interpretation rules but is also reflected in the practice of international dispute settlement. However, despite this legal foundation, no ECT tribunal has yet incorporated international climate law into its decisions. While practical challenges and uncertainties persist, precedents from broader international dispute settlement and climate litigation suggest that ECT arbitration could evolve to balance investment protection with climate commitments. This article argues that fostering an integrative interpretative approach could enable ISDS to serve both investment stability and climate mitigation goals, contributing to a more coherent legal framework for energy transition.